Biphasic Potassium Contractures in Frog Muscle Fibers - Costantin, L. L. (The Rockefeller University Press, 1971)
Potassium-induced contractures were studied in single fibers from the semitendinosus muscle of Rana pipiens. Contractures elicited by solutions containing 60–117 mM potassium and 120 mM chloride were biphasic, consisting of a rapid initial contraction with a duration at 23°C of less than 1 sec followed by a slow response with a duration of many seconds. At 13°C, the initial response was greatly prolonged so that the two responses virtually fused into a single smooth contracture. Membrane potential in high potassium, high chloride solutions underwent a transient peak depolarization, probably as a result of time-dependent changes in membrane conductance during depolarization. It is proposed that this complex time course of depolarization gives rise to the biphasic contracture response.